Pharmacotherapy of bone metastases in breast cancer patients – an update. (June 2014) - Jacobs, Carmel; Simos, Demetrios; Addison, Christina; Ibrahim, Mohammed; Clemons, Mark
Abstract : Introduction: Bone metastases in breast cancer patients are a common clinical problem and pose a threat to the quality of life of such patients. Multiple randomized trials have demonstrated the benefit of both bisphosphonates and denosumab in reducing the incidence and delaying the onset of skeletal related events (SREs) in breast cancer patients with bone metastases. Areas covered: We review the current literature on the use of bisphosphonates and denosumab along with strategies to maximize benefit and minimize risk of these agents. We also review potential future targets. Expert opinion: Despite the potent osteoclast inhibiting effects of the bone-targeted agents in current clinical use, we have likely maximized their ability to inhibit SREs and must in turn focus on minimizing their potential toxicity. The future will likely involve more novel treatment strategies as well as the development of new agents. The current 'one size fits all' approach for the management of breast cancer bone metastases will be replaced by 'tailored' treatment for each individual patient as we usher in the era of 'personalized medicine.' In addition, new bone-targeted agents (e.g., sclerostin inhibitors) and combinations will continue to be explored, as will the evaluation of the bone-targeting properties of more conventional non-osteoclast targeting therapies.